Sistem Pendukung Keputusan Penentuan Kelas Unggulan Pada Siswa baru di SMK Negeri Menggunakan Metode SMART (STUDI KASUS: SMK NEGERI 1 BINJAI) - Kiki Angel; Novriyenni Novriyenni; Anton Sihombing (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Excellent class students are students who consist of selected people who have more outstanding abilities when compared to ordinary class students. SMK N 1 Binjai is one of the schools that has implemented a superior class selection where every year the school selects new students to enter the superior class. The selection process is still using a manual system. Selection in this way will take a long time so it is not effective and efficient. This system is designed using the Simple Multi-Attribute Rating Technique (SMART) method where each criterion is given a weight and then calculated using the SMART formula. This multi-criteria decision-making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important the criterion is with other criteria. The results of the research are in the form of a recommendation system output for students who will enter the superior class. The benefit of this research is that it provides media for decision-making information for the school to decide which students are eligible to enter the superior class.